Cross-sectional associations between accelerometry-measured physical activity, left atrial size, and indices of left ventricular diastolic dysfunction: The Tromsø Study - Heitmann, Kim Arne; Løchen, Maja-Lisa; Hopstock, Laila Arnesdatter; Stylidis, Michael; Welde, Boye; Schirmer, Henrik; Morseth, Bente (Preventive Medicine Reports, 2020)
Whereas left atrial (LA) enlargement is an independent predictor for adverse cardiovascular events and all-cause mortality, this is regarded a physiological adaption of exercise. Paradoxically, LA size in athletes may overlap the enlargement observed in patients with cardiac pathology. Current knowledge is mainly derived from studies of athletes, and little is known about cardiac adaptations to physical activity (PA) in the general population. We explored the association between objectively measured PA and LA volume index (LAVi), and between LAVi enlargement and indices of diastolic dysfunction stratified by PA-level. Our study included 1573 participants from the population-based Tromsø Study (2015–16). PA was assessed with an ActiGraph wGT3X-BT accelerometer. Echocardiography was performed according to current guidelines. The associations between PA and LAVi, and between LAVi enlargement and indices of diastolic dysfunction were estimated by univariable and multivariable linear regression analyses, adjusted for sex, age, and cardiovascular risk factors. Our multiple adjusted analyses showed significant linear associations between PA and LAVi in ages < 70 years, and between PA and LAVi in participants with normal diastolic function. No associations were seen in ages ≥ 70 years or for participants with abnormal diastolic function. In those 40–54 years, the most active participants had larger LAVi (4.45 mL/m 2 , p = 0.016) than the least active. LAVi enlargement was only associated with indices of diastolic dysfunction in the most inactive participants. In conclusion, higher levels of PA associate with greater LAVi in participants < 70 years with normal diastolic function. LAVi enlargement is only associated with diastolic dysfunction in the most inactive participants.